Representasi Hubungan Manusia dan Lingkungan melalui Simbolisme Alam dalam Novel The Old Man and The Sea: Kajian Ekokritik - Dini Sela Fitrianingrum (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to examine the representation of the relationship between humans and the environment through natural symbolism in Ernest Hemingway novel The Old Man and the Sea. This novel was chosen because it depicts nature not merely as a setting for the story, but as a meaningful entity that forms a complex relationship with the main character, Santiago. This study employs a descriptive qualitative method using Greg Garrard ecocritical approach. The research data consists of textual quotations containing natural symbolism such as the sea, birds, fish, sharks, the sun, and stars obtained through close reading and note-taking. Data analysis was conducted by identifying symbols of nature, interpreting their symbolic meanings, and classifying the forms of human-environment relationships based on Garrard ecocritical themes, namely the pastoral, animals, and wilderness. The results of the study indicate that the symbolism of nature in the novel represents three forms of human-environment relations: kinship, ambivalence, and conflict. Kinship is characterised by emotional closeness and the recognition of nature as an integral part of human life. Ambivalence arises from the dilemma between respect for nature and the human need for survival. Meanwhile, conflictual relationships are depicted through the power of the wild, which underscores human limitations. This study concludes that the novel The Old Man and the Sea represents the relationship between humans and the environment as a dynamic, ethical, and non-anthropocentric one